A Theoretical Discussion on The Relationship Between Cultural Intelligence and Effective Leadership - Aden, Abdishukri Rashid; Başar, Ufuk (Contemporary Business and Economic Issues II, 2023)
The aim of this chapter was to discuss the relationship between cultural intelligence and effective leadership and make some implications. Today, organizations strive to be international. This forces them to function in diverse cultural settings. However, organizations face challenges in trying to create synergy among their employees who are from various cultural and geographical settings. Studies have shown that cultural intelligence is important in building effective global organizations around these differences. Cultural intelligence helps leaders to understand, appreciate, embrace, and effectively lead a culturally diverse organization. Therefore, it can have a significant role in the display of effective leadership behaviors.